Bacterial Cellulose Nanofibrillar Patch as a Wound Healing Platform of Tympanic Membrane Perforation. Issue 11 (4th April 2013) - Kim, Jangho; Kim, Seung Won; Park, Subeom; Lim, Ki Taek; Seonwoo, Hoon; Kim, Yeonju; Hong, Byung Hee; Choung, Yun‐Hoon; Chung, Jong Hoon
Abstract Bacterial cellulose (BC)‐based biomaterials on medical device platforms have gained significant interest for tissue‐engineered scaffolds or engraftment materials in regenerative medicine. In particular, BC has an ultrafine and highly pure nanofibril network structure and can be used as an efficient wound‐healing platform since cell migration into a wound site is strongly meditated by the structural properties of the extracellular matrix. Here, the fabrication of a nanofibrillar patch by using BC and its application as a new wound‐healing platform for traumatic tympanic membrane (TM) perforation is reported. TM perforation is a very common clinical problem worldwide and presents as conductive hearing loss and chronic perforations. The BC nanofibrillar patch can be synthesized from Gluconacetobacter xylinus; it is found that the patch contained a network of nanofibrils and is transparent. The thickness of the BC nanofibrillar patch is found to be approximately 10.33 ± 0.58 μm, and the tensile strength and Young's modulus of the BC nanofibrillar patch are 11.85 ± 2.43 and 11.90 ± 0.48 MPa, respectively, satisfying the requirements of an ideal wound‐healing platform for TM regeneration. In vitro studies involving TM cells show that TM cell proliferation and migration are stimulated under the guidance of the BC nanofibrillar patch. In vivo animal studies demonstrate that the BC nanofibrillar patch promotes the rate of TM healing as well as aids in the recovery of TM function. These data demonstrate that the BC nanofibrillar patch is a useful wound‐healing platform for TM perforation.